(untitled) (Research, Society and Development, 2025)
Climate change represents the greatest challenge to human survival in the 21st century, severely impacting biodiversity and natural resources at the global and regional levels. In Ecuador, a megadiverse country, these transformations are manifested in a sustained increase in temperature, variability in precipitation patterns, and the recurrence of extreme events such as El Niño and La Niña. These alterations have led to the reduction of forested areas, the retreat of glaciers, and the degradation of emblematic ecosystems such as Chocó and the Galapagos Islands, severely affecting endemic species and essential resources. Permanent agriculture is the main driver of deforestation, exacerbating the vulnerability of key ecosystems such as páramos, cloud forests, and mangroves, and threatening groups such as amphibians and marine mammals. This systematic research aims to assess the vulnerability of Ecuador’s biodiversity and natural resources to climate change, in order to propose effective conservation and adaptation measures. The study, with a bibliographic approach and a mixed-method design, confirms that habitat loss, species decline, and altered hydrological cycles impact community food security, health, and economic well-being. To strengthen socioecological resilience, it is crucial to implement region-specific adaptive strategies, accompanied by robust environmental management and active community participation.